Formation mechanism of climate warming-induced landslides in permafrost along the Qinghai-Tibet Engineering corridor - Wei, Tao; Wang, Jiao; Xie, Ming; Feng, Peihua (Frontiers in Earth Science, 2024)
The Qinghai-Tibet Plateau (QTP) has undergone substantial warming, resulting in extensive permafrost degradation and a pronounced increase in landslide frequency. However, the causal link between climate warming and permafrost landslide occurrences remains poorly understood. A comprehensive inventory of permafrost landslides along the Qinghai-Tibet Engineering Corridor (QTEC) from 2016 to 2022 was compiled through remote sensing and field verification, along with an analysis of landslide triggering factors based on data from 5 weather stations, 4 active layer thickness observation sites, and 3 precipitation stations. From 2000 to 2020, the mean annual air temperature (MAAT) showed an increase of 0.5°C per decade, while precipitation remained relatively stable. A notable peak occurred in 2016, with MAAT and mean annual surface ground temperature rising sharply by 0.59°C and 0.41°C, respectively, from the previous year. In the same year, active layer thickness across observation sites increased by an average of 18.5 cm, exceeding the average thickening rate. This substantial deepening of the active layer suggests that a portion of the underlying permafrost, potentially ice-rich near the permafrost table, thawed during the warm season. Laboratory experiments further reveal a three-stage reduction in soil strength as temperatures approach 0°C, with the most pronounced decline at −1°C. Interpretation of landslide data shows that landslide frequency in 2016 significantly increased, reaching approximately 1.3 times the historical total. This suggests that a thawed interlayer forming at the active layer-permafrost interface plays a dominant role in landslide initiation. The thawed layer acts as a weak zone, enabling the downward movement of the overlying active layer and contributing to slope instability. These findings provide robust evidence linking temperature rise to permafrost-related landslides, offering new insights into the mechanisms of temperature-induced slope instability in high-altitude regions.